Foxo3a-Mediated DNMT3B Impedes Cervical Cancer Cell Proliferation and Migration Capacities through Suppressing PTEN Promoter Methylation. Issue 1 (31st December 2023) - Li, Hongying; Yuan, Yuqin; Dong, Hong; Wang, Tinghui; Zhang, Dunlan; Zhou, Limin; Chen, Lu; He, Xueyan
Abstract: Objective: Cervical cancer is linked with the constitutive activation of growth factors and gene mutations-induced pro-survival signaling pathways. Herein, we purposed to explore the possible molecular mechanism of Foxo3a-mediated DNMT3B in the proliferation and migration of cervical cancer cells via mediating the PTEN promoter methylation. Methods: Foxo3a expression in cervical cancer was tested by qRT-PCR and western blot experiments. The cervical cancer cell biological functions with overexpression of Foxo3a were evaluated by CCK-8 assay, Transwell experiment, and flow cytometry, respectively. MS-PCR was utilized for testing the PTEN methylation levels, and ChIP experiment was implemented for evaluating the enrichment of DNMT3B in the PTEN promoter region and the binding of Foxo3a and DNMT3B. The PTEN methylation and interference with Foxo3a expression were performed in cervical cancer cells, and then their impacts on cervical cancer cell biological functions were observed. Results: FOXO3a was expressed at a low level in cervical cancer, and its overexpression contributed to a reduction in cell proliferative, migratory and invasive capabilities, and an elevation in apoptosis rate. Foxo3a blocked its methylation with the PTEN promoter by repressing DNMT3B activity. Upon treatment with methyltransferase inhibitor (5-aza-dc), the malignant phenotypes of cervical cancer cells were diminished. 5-aza-dc neutralized the impacts of silencing Foxo3a on malignant phenotypes. Conclusion: This research underlines that Foxo3a blocks its methylation with the PTEN promoter by inhibiting DNMT3B activity, which subsequently impedes cervical cancer cell progression.